Cleavage of lamin A by Mch2 alpha but not CPP32: multiple interleukin 1 beta-converting enzyme-related proteases with distinct substrate recognition properties are active in apoptosis. - Takahashi, A (1996)
Although proteases related to the interleukin 1 beta-converting enzyme (ICE) are known to be essential for apoptotic execution, the number of enzymes involved, their substrate specificities, and their specific roles in the characteristic biochemical and morphological changes of apoptosis are currently unknown. These questions were addressed using cloned recombinant ICE-related proteases (IRPs) and a cell-free model system for apoptosis (S/M extracts). First, we compared the substrate specificities of two recombinant human IRPs, CPP32 and Mch2 alpha. Both enzymes cleaved poly-(ADP-ribose) polymerase, albeit with different efficiencies. Mch2 alpha also cleaved recombinant and nuclear lamin A at a conserved VEID decreases NG sequence located in the middle of the coiled-coil rod domain, producing a fragment that was indistinguishable from the lamin A fragment observed in S/M extracts and in apoptotic cells. In contrast, CPP32 did not cleave lamin A. The cleavage of lamin A by Mch2 alpha and by S/M extracts was inhibited by millimolar concentrations of Zn2+, which had a minimal effect on cleavage of poly (ADP-ribose) polymerase by CPP32 and by S/M extracts. We also found that N-(acetyltyrosinylvalinyl-N epsilon-biotinyllysyl)aspartic acid [(2,6-dimethylbenzoyl)oxy]methyl ketone, which derivatizes the larger subunit of active ICE, can affinity label up to five active IRPs in S/M extracts. Together, these observations indicate that the processing of nuclear proteins in apoptosis involves multiple IRPs having distinct preferences for their apoptosis-associated substrates.